2016
DOI: 10.1016/j.amjmed.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipid Profile of Obese Patients Following Contemporary Bariatric Surgery: A Meta-Analysis

Abstract: Background Although metabolic surgery was originally performed to treat hypercholesterolemia, the effects of contemporary bariatric surgery on serum lipids have not been systematically characterized. Methods and Results MEDLINE, EMBASE and Cochrane databases were searched for studies with ≥20 obese adults undergoing bariatric surgery [Roux-en-Y Gastric Bypass (RYGBP), Adjustable Gastric Banding, Bilio-Pancreatic Diversion (BPD), or Sleeve Gastrectomy]. The primary outcome was change in lipids from baseline t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 28 publications
13
47
0
2
Order By: Relevance
“…The LSG procedure appeared to have a reductive effect in medium serum levels of atherosclerosis-promoting lipid factions (TG, LDL, TC), wherein the observed serum level of the protective HDL fraction rose during the follow-up. Improvements in lipid metabolism caused by bariatric procedures are known in the scientific literature, but each operation technique induce changes with different intensity; thus an appropriate procedure should be selected for dyslipidemia severity in the patient [33,34]. During the follow-up we also observed pleiotropic improvements in many other obesity-related comorbidities, like other authors assessing patients after bariatric surgery [35,36].…”
Section: Niddm Arterial Hypertension Partial Remission (%)supporting
confidence: 56%
“…The LSG procedure appeared to have a reductive effect in medium serum levels of atherosclerosis-promoting lipid factions (TG, LDL, TC), wherein the observed serum level of the protective HDL fraction rose during the follow-up. Improvements in lipid metabolism caused by bariatric procedures are known in the scientific literature, but each operation technique induce changes with different intensity; thus an appropriate procedure should be selected for dyslipidemia severity in the patient [33,34]. During the follow-up we also observed pleiotropic improvements in many other obesity-related comorbidities, like other authors assessing patients after bariatric surgery [35,36].…”
Section: Niddm Arterial Hypertension Partial Remission (%)supporting
confidence: 56%
“…Apparently only RYGB, but not gastric banding [68] or gastric sleeve gastrectomy [69], is associated with reduced absorption of cholesterol. A recent systematic review and meta-analysis demonstrated that LDL-cholesterol was reduced significantly after gastric bypass (0.64 mmol/l) and biliopancreatic diversion (1.17 mmol/l), while the LDL-lowering effects of gastric banding (0.23 mmol/l) and sleeve gastrectomy (0.20 mmol/l) were small or non-significant [70]. To conclude, the beneficial effect of bariatric surgery on triglyceride and HDL-cholesterol levels seems to be weight loss-dependent while the improvement in LDL-cholesterol levels after gastric bypass surgery is at least partly weight loss-independent.…”
Section: Management Of Co-morbiditiesmentioning
confidence: 99%
“…(11) A meta-analysis of the impact of bariatric surgery on lipid profile also did not find that TC improved significantly. (9) One possible explanation is that outcomes were procedure-related. The majority of our subjects underwent sleeve gastrectomy, but Roux-En-Y gastric bypass (RYGB) has been shown to be more effective in lowering lipid level.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies are based on followup data of two years' duration or less. (9) Both the intermediate and long-term impact of bariatric surgery on hyperlipidaemia and its comorbidities are limited, especially in the Asian population. (10) We aimed to evaluate the impact of bariatric surgery on lipid profile, glycaemic control and weight loss at five-years' follow-up.…”
Section: Introductionmentioning
confidence: 99%